Umkm Berbasis Digital Marketing Di Desa Perbawati Sukabumi - Dadan Rahmat; Ali Rofi (Universitas Muhammadiyah Sukabumi, 2022)
A maximum 200 word abstract in English in italics with Arial 10 point, single space. Abstract should be clear, descriptive, and should provide a brief overview of the problem studied. Abstract topics include reasons for the selection or the importance of research topics, mention the community service partner, research methods and a summary of the results. Abstract should end with a comment about the importance of the results or conclusions brief.